Pengembangan Multimedia Interaktif Berbasis Komputer dalam Meningkatkan Hasil Belajar Kognitif di Sekolah Dasar - Agustina, Riza (Program Studi Pendidikan Guru Sekolah Dasar, 2024)
This development research uses the ADDIE research model, with 5 stages, namely analysis, design, development, implementation and evaluation. The subjects of this study are 15 students in class 5B of SDN Curahmalang 2, Jombang Regency with 6 students for small group trials and 20 students for field tests. The results of the study show that. 1) The results of computer-based interactive multimedia validity were obtained from media expert validators 93.3%, material validation 93.3%, and learning design validation 90%, with an average percentage of expert validation of 92.9%, which stated that it was very valid for use. The results of the data on student attractiveness of small group trials showed 100% interest, 100% field tests, and the results of teacher response questionnaires of 100% interesting to use. 1) The results of computer-based interactive multimedia validity were obtained from media expert validators 93.3%, material valid ation 93.3%, and learning design validation 90%, with an average percentage of expert validation of 92.9%, which stated that it was very valid for use. 2) The results of the data on student attractiveness of small group trials showed 100% interest, 100% fi eld tests, and the results of teacher response questionnaires of 100% interesting to use.3) . The results of effectiveness showed effective use in terms of small group trials with the results of observing student activities by 78.7%, teacher observation ac tivities by 95.8%, and student learning outcomes by 100%. While field tests showed 78.7% of the results of observations of student activities, 95.8% of teacher activities, and 90% obtained from student learning outcomes. This research is expected to motiva te teachers to create or develop media and optimize the use of technology in learning media.